Association between vitamin D deficiency and insulin resistance markers in euthyroid non-diabetic individuals - Urrunaga Pastor, Diego (2018)
Aim: To evaluate the association between vitamin D deficiency and insulin resistance (IR) or hyperinsulinemia after oral glucose tolerance test (OGTT) in euthyroid non-diabetic individuals. Materials and methods: We carried out an analytical cross-sectional study in euthyroid non-diabetic adults of both sexes, who attended the outpatient service of a private clinic in Lima-Peru during the 2012e2016 period. Participants were categorized in two groups according to their serum vitamin D levels: normal vitamin D levels (serum vitamin D values 20 ng/dL) and vitamin D deficiency (serum vitamin D values < 20 ng/dL). IR was defined as a Homeostasis Model Assessment (HOMA-IR) value 3.8 and hyperinsulinemia after OGTT was defined as a serum insulin value 80mU/mL after 120min of 75-g glucose intake. We elaborated crude and adjusted Poisson regression models to assess the association between serum vitamin D levels and IR or hyperinsulinemia after OGTT. The reported association measure was the prevalence ratio (PR) with their respective 95% confidence intervals (95%CI). Results: We analyzed 204 participants, the average age was 38.5 ± 10.6 (SD) years, 40 (19.6%) were males and the vitamin D median was 25.0 (IQR: 19.0e33.3) ng/dL. The prevalence of vitamin D deficiency, IR and hyperinsulinemia after OGTT was 29.4% (n ¼ 60), 29.9% (n ¼ 61) and 25.0% (n ¼ 51). In the adjusted Poisson regression models, the prevalence of hyperinsulinemia after OGTT was higher among the vitamin D deficient group (aPR¼1.75; 95%CI: 1.06e2.90); however, we did not find statistically significant association between vitamin D deficiency and IR (aPR¼0.99; 95%CI: 0.61e1.63). Conclusions: We found an association between vitamin D deficiency and hyperinsulinemia after OGTT in euthyroid people with no T2DM.Our findings are consistent with previous reports; providing evidence that serum vitamin D deficiency could be an IR marker.